In vitro anti-microbial and in vivo cytokine modulating effects of different prepared Chinese herbal medicines - Lin, S.; Chen, C; Lin, S.; Chou, M.; Shih, H.; Lee, I.; Kao, C.; Kao, C.; Chen, F.; Ho, Y.; Hsieh, K.; Huang, C.; et al.
The toxicity, antimicrobial and cytokine modulating effects of herbal medicines in treating periodontal diseases were evaluated in this study. Using the broth dilution method and disc agar diffusion test, in individual and combined decocted preparations, different concentrations of Ching-Wei-San and its individual herbal components, Coptidis rhizoma, Angelicae sinensis radix, Rehmanniae radixet rhizom, Moutan radicis cortex, and Cimicifuga foetida, were tested for in vitro inhibitory effects on three well-known plaque-causing bacteria, Porphyromonas gingivialis, Streptococcus sanguis, and Streptococcus mutans, and two common pathogens, Staphylococcus aureus and Escherichia coli. The cytokine modulating effects were evaluated in Balb/c mice. The results suggested that one milliliter Ching-Wei- San at the 25,000 mg/mL concentration daily for the mice had significantly high levels in the liver function indexes in the 3-day acute toxicity test and in both the liver and kidney function indexes in the 28-day subacute toxicity test (P < 0.01). The 250 mg/mL Ching- Wei-San is comparable to 250 mg/mL of tetracycline, and had similar inhibitory effects on the tested bacteria. Coptidis rhizoma (62.5 mg/mL)was the only individual herbal component to show 100
Keywords: COPTIDIS RHIZOMA; ANGELICAE SINENSIS RADIX; REHMANNIAE RADIXET RHIZOM; MOUTAN RADICIS CORTEX; CIMICIFUGA FOETIDAX; PERIODONTAL DISEASE